Five little pumpkins - Yaccarino, Dan ([New York] : HarperFestival, 1998)
The traditional finger rhyme illustrated with lively paintings.
"Harper growing tree"--Cover p. [4].
Cover title.
On board pages.
K-3
Keywords: Counting-out rhymes -- Juvenile literature; Finger play -- Juvenile literature; Halloween -- Juvenile literature; Counting-out rhymes; Finger play; Halloween; Counting-out rhymes; Finger play; Halloween